2016
DOI: 10.3400/avd.oa.16-00036
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Selective Use of Intraluminal Shunt in Carotid Endarterectomy: a Study of 122 Cases

Abstract: Objectives:To assess the advantage of selective use of shunt in carotid endarterectomy (CEA) under local anesthesia. Materials and Methods: A total of 122 consecutive patients fulfilling international guidelines were included. Shunt was used selectively only in cases of bilateral severe carotid artery occlusive disease or in those patients who developed neurological symptoms on clamping of carotid artery. Follow up was done weekly for one month; then every month for 3 months; and then every 3 months for a year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…In our study, shunts were used in 93.8% patients receiving GA and 18.5% in patients with RA. Although the use of a shunt is common practice and should protect the brain from stroke [26,27], intraoperative shunt placement is a strong predictor of perioperative strokes [28].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, shunts were used in 93.8% patients receiving GA and 18.5% in patients with RA. Although the use of a shunt is common practice and should protect the brain from stroke [26,27], intraoperative shunt placement is a strong predictor of perioperative strokes [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, improperly placed shunts may cause embolisms. M. Jamil et al showed that routine shunt use did not affect perioperative results [12]. On the other hand, there are studies indicating that selective and routine shunt use reduce the incidence of stroke [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a shunt has many potential disadvantages, including dislodgement and air or plaque embolism, requiring extra time for insertion and removal, longer arteriotomy, and poor cost effectiveness [ 14 ]. One study included 122 consecutive patients with a mean procedure time of 170 min in patients in whom a shunt was used compared with 100 min in patients without a shunt (P=0.003) [ 15 ]. Another study of 59 patients showed that conventional use of a carotid shunt tube in carotid endarterectomy (CEA) for extracranial carotid stenosis treatment does not reduce the risk of perioperative complications [ 16 ].…”
Section: Discussionmentioning
confidence: 99%